Research Collaborative on Cash Transfers and Intimate Partner Violence - CGIAR Research Program on Policies, Institutions, and Markets (2019)
In 2019, the Collaborative's work was cited and drawn upon in a number of high-level guidance documents (DFID's "What Works to Prevent Violence against Women and Girls" programme, the World Health Organization's RESPECT Women framework...)